The Legacy of Women in Theological Education in Kenya - Kihuha, Mary Wanjiku (2023)
Mary Wanjiku Kihuha is a lecturer at Pan-Africa Christian University Kenya School of Theology and Biblical Studies, a Nagel Institute research grantee as well as a member of the Circle of Concerned African Women Theologians.
free